First Russian experience of liver and kidneys transplantation obtained from the donor with out-of-hospital irreversible cardiac arrest - A. E. Skvortsov; S. F. Bagnenko; S. S. Komedev; V. M. Teplov; I. I. Kolachev; A. Yu. Shchurov; A. L. Merkulov; V. P. Filatov; A. A. Boykov; O. N. Reznik (Вестник трансплантологии и искусственных органов, 2019)
Organs’ shortage remains the main limiting problem for accessibility of organ transplantation. There is the growing interest among transplant society for use organs obtained from «uncontrolled» donors after cardiac death (uDCDs), or, asystolic donors. But the warm ischemic time is critical factor for wide accepting of practice of transplantation such kind of organs. The article presents the first case of successful clinical organ transplants from the donor with out-of-hospital irreversible cardiac arrest obtained with help of life support devices.